Regulatory Mechanisms of the Wnt/β-Catenin Pathway in Diabetic Cutaneous Ulcers - Zhang, Han; Nie, Xuqiang; Shi, Xiujun; Zhao, Jiufeng; Chen, Yu; Yao, Qiuyang; Sun, Chengxin; Yang, Jianwen (Frontiers in Pharmacology, 2018)
ABSTRACT Skin ulcers were one of the serious complications of diabetes. Diabetic patients always suffer from the vascular lesions and complications of peripheral neuritis, peripheral vascular lesions and collagen abnormalities, which result in skin wounds that were refractory and often develop into chronic ulcers. Healing of diabetic skin ulcers mainly involves an inflammatory reaction, wound proliferation, remodeling regulation and control of stem cells. Since 2005, the development of molecular biology has allowed for a more in-depth study of diabetic skin ulcers. The Wnt/β-catenin pathway is a classic highly conserved signal transduction pathway involved in a variety of biological processes such as cell proliferation, apoptosis, and differentiation. It is considered as one of the important pathways involved in the healing of skin wounds. This article not only summarizes the mechanism of Wnt/β-catenin pathway in the inflammatory response of diabetic ulcer wounds, wound proliferation, wound remodeling, and stem cells, but also discusses the existence of interactions between the Wnt signal pathway and other pathways.